2021
DOI: 10.17921/2447-8938.2021v22n3p223-229
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Mothers towards Infant Oral Health Care in Their Children’s First Year of Life

Abstract: This study aimed to assess mothers’ oral health-related knowledge and practices in immediate and late puerperium, and in the child’s first year of life. This study is a prospective cohort study, in which data were collected from 358 mothers of children born between 2013 and 2014, in immediate and late puerperium, and in children’s first year of life, by interviews with sociodemographic characterization and oral health questionnaires, and were analyzed by descriptive statistics and Chi-square test (α = 5%). Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This study reported that knowledge score of the mothers was good in 29.3%, fair knowledge in 38.7%, and poor in the remaining 32% as shown in (Figure 1). A different result observed in Jaafar et al,2018 study in Lebanon, in which based on the total score category calculation the results showed that, most of the expected mothers (69.5%) had fair, while 17.4% had poor, and 13.1% had good knowledge (6,7,8) .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This study reported that knowledge score of the mothers was good in 29.3%, fair knowledge in 38.7%, and poor in the remaining 32% as shown in (Figure 1). A different result observed in Jaafar et al,2018 study in Lebanon, in which based on the total score category calculation the results showed that, most of the expected mothers (69.5%) had fair, while 17.4% had poor, and 13.1% had good knowledge (6,7,8) .…”
Section: Discussionmentioning
confidence: 65%
“…In Chala et al,, 2018 study in Morocco, the adjusted linear regression model showed that the knowledge score was significantly related to mother's age (P < 0.001), education level (P < 0.001) (9) . Rossato et al, study in Brazil, in 2021 reported that Mothers' knowledge score was associated with sociodemographic parameters, being those mothers aged from 20 to 29 years and with higher education who presented higher levels of oral health care knowledge (6) .…”
Section: Discussionmentioning
confidence: 99%